Two Senatorial Families from Klaudiupolis - Mustafa Adak (Gephyra, 2007)
Two Senatorial Families from KlaudiupolisA brief inscription on a pedestal found in the town centre of Bolu refutes the previously dominant view about the provenance of Marcus Ulpius Arabianus, consul suffectus in the late Antoninian period and afterwards governor of Syria Palaestina and Africa proconsularis. He did not hail from Amastris, where he had good, probably inherited connections, but from Klaudiupolis, where according to the new inscription he honoured his uncle M. Ulpius Aristaeus with a statue. Aristaeus in turn also erected a statue in Klaudiupolis in honour of an imperial valet. The consul's son, who is attested to have been legatus Asiae under Septimius Severus, was M. Ulpius Domitius Aristaeus Arabianus. This name clearly shows that he had adopted not only the cognomina of his father and his uncle, but also the name Ulpius and another nomen gentile (Domitius). From this composite name the author concludes that the senator had married a woman from the gens Domitii. He also assumes that this woman stems from a senatorial family, so that the marriage was of appropriate social standing. In Bithynia, this assumption is satisfied only by M. Domitius Euphemus and his family, which also came from Klaudiupolis. There were probably no further senatorial families in this small town in eastern Bithynia in the Antonine-Severian period. As a well-known inscription from the Phrygian town of Pyrmnessos shows, the consul's son used only the shortened name of Domitius Aristaeus Arabianus. He seems to have preferred his mother's nomen gentile, probably because the Domitii were more prominent and had had Roman citizenship for a much longer time. Adak also believes that Arabianus is identical with the senator Domitius Arabianus attested as archon in Athens under Severus Alexander. Apart from Flavius Arrianus, this would give us another Bithynian senator who after a successful career in the service of the emperor settled down in Athens, where he took over the office of archon to enhance his prestige.